PENGARUH FASILITAS, KUALITAS PELAYANAN DAN PENGALAMAN TERHADAP KEPUASAN KONSUMEN PENGINAPAN CITRA ALAM 2 KOTA SUNGAI PENUH - Zefri Efdison; Yelnim Yelnim; Dorris Yadewani; Erni Febrina Harahap; Aan Nurmadi (Juremi: Jurnal Riset Ekonomi, 2023)
This study aims to determine the Effect of Facilities, Service Quality and Experience on Consumer Satisfaction of Citra Alam Inn 2 Full River City. The sample from this study was 80 people. Data were collected with questionnaires that had been tested for validity and reliability. The data analysis techniques used are analysis, descriptive, multiple regression, coefficient of determination and hypothesis testing using the t test and the F test. The results showed that there was a significant influence between facilities on consumer satisfaction of Citra Alam Inn 2, this was evidenced by t count > t table (3.101 > 1.99167), and with significance value = 0.041 < 0.05, and the magnitude of influence was 22.8%. There is a significant influence between the Quality of Service on Consumer Satisfaction of Citra Alam Inn 2, this is evidenced by t count > t table (2.066 > 1.99167), and with significance value = 0.000 < 0.05, and the magnitude of influence is 14.4%. There is a significant influence between Experience and Consumer Satisfaction of Citra Alam Inn 2, this is evidenced by t count > t table (2.498 > 1.99167), and with significance value = 0.000 < 0.05, and the magnitude of influence is 15.5%. There is a significant influence between Facilities, Quality of Service and Experience on Consumer Satisfaction of Citra Alam Lodging 2 simultaneously or together, this is evidenced by F count > F table (28,222 > 2.72) or sig < α (0.000 < 0.05), and the magnitude of the influence is 52.7%, while the rest (100% - 52.7%), i.e. 47.3% is explained by other causal factors not studied in this study.